Du consentement à la délibération : une critique communicationnelle du marketing politique - Éric Dacheux (Communiquer, 2016)
This article aims to lay out a new scientific approach to public communication. Today, this area is effectively dominated by political marketing. However, the more such a marketing approach prevails, the more citizens tend to distrust their own institutions. The thesis advanced by this article is that such institutions would do well to distinguish more clearly between communication, marketing and manipulation in their political communications, a clarification that leads to a change in strategic objective: not to draw institutions closer to their publics, but to foster a common culture respectful of the cultural diversity of individuals, while creating an “integrative conflict.” We call this a deliberative approach to public communications. The latter is based, not on North American work on persuasive communication, argumentation, or deliberation, but French-language work on the subject of incommunication.